PRAKTIK PEMBAGIAN HARTA WARIS SEBELUM MUWARIS MENINGGAL DUNIA DI DUSUN BOGELAN DESA SUKOREJO KECAMATAN MOJOTENGAH - FAJAR FITRIYANI (Hukum Keluarga Islam, 2022)
Islam regulates all aspects of life, one of which is the issue of inheritance. In Islam, the division of inheritance is held with the aim that the property can be re-managed in order to bring benefits. In Islamic law inheritance is distributed after the muwaris dies, but in practice there is a mention of inheritance in the distribution of assets before the muwaris dies. It should be underlined that this is only a form of parental love for their children. Therefore, the authors conducted a study with the aim of knowing the practice of dividing inheritance before the inheritance died in Bogelan Hamlet, Sukorejo Village, Mojotengah District, Wonosobo Regency by being studied based on Islamic law. The data obtained are through observation, interviews, and documentation. After the data is collected then it is described and concluded in an inductive way. The results showed that most of the people of Bogelan Hamlet, Sukorejo Village, Mojotengah District, Wonosobo Regency did the distribution of inheritance to the heirs before the muwaris died this was done because of the culture in the village. The researcher selected 10 samples and it can be concluded that the practice of inheritance distribution using the principle of sepekol segendhongan is the same as the Islamic principle between men and women is 2:1. According to Islamic law, the practice is categorized as a grant or testament because the muwaris has not died while the inheritance is distributed when the muwaris have died.